2009
DOI: 10.1007/s00726-009-0440-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of residue-level photo-oxidative damage in peptides

Abstract: Protein and peptide oxidation is a key feature in the progression of a variety of disease states and in the poor performance of protein-based products. The present work demonstrates a mass spectrometry-based approach to profiling degradation at the amino acid residue level. Synthetic peptides containing the photosensitive residues, tryptophan and tyrosine, were used as models for protein-bound residue photodegradation. Electrospray ionisation tandem mass spectrometry (ESI-MS/MS) was utilised to characterise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 70 publications
7
55
2
Order By: Relevance
“…In Table 5, it can be concluded that the photodegradation rate of tyrosine was positively correlated with the change rate of the whiteness of silk fibroin, which means that tyrosine content of silk fibroin decreased with the increase in photoyellowing of silk fibroin (Grosvenor, Morton, & Dyer, 2010). Since the change rate of the whiteness of silk fibroin was always higher than the photodegradation rate of tyrosine, it can be deduced that photochemistry reactions of tyrosine were directly related to the photoyellowing of silk fibroin and photochemistry reactions of some other amino acids were also involved in the photoyellowing progress at the same time Xie, Shao, & Zhen, 1993).…”
Section: Effects Of the Irradiancy On The Photoyellowing Of Silk Fibroinmentioning
confidence: 92%
“…In Table 5, it can be concluded that the photodegradation rate of tyrosine was positively correlated with the change rate of the whiteness of silk fibroin, which means that tyrosine content of silk fibroin decreased with the increase in photoyellowing of silk fibroin (Grosvenor, Morton, & Dyer, 2010). Since the change rate of the whiteness of silk fibroin was always higher than the photodegradation rate of tyrosine, it can be deduced that photochemistry reactions of tyrosine were directly related to the photoyellowing of silk fibroin and photochemistry reactions of some other amino acids were also involved in the photoyellowing progress at the same time Xie, Shao, & Zhen, 1993).…”
Section: Effects Of the Irradiancy On The Photoyellowing Of Silk Fibroinmentioning
confidence: 92%
“…Recent investigations on Trp damage via UV irradiation uncovered that a large variety of photoproducts coexist with multiple oxidations taking place at the Trp residue (up to 4), providing a cascade of modifications [57]. Photodamage is an important artifact to carfully monitor in any laser study.…”
Section: Notesmentioning
confidence: 99%
“…Both redox and Maillard chemistries generate a range of products in susceptible protein regions, and it is the type and abundance profile of these multiple products that results in the overall food properties. Changes in relative abundance in mass spectrometric analysis can be used to track the progressive loss of native peptides and proteins of parent peptides, and the corresponding formation of modification products within those proteins and peptides (Grosvenor et al, 2009). This can be used to evaluate differing protein processing or treatment parameters, as wells as monitor variation under a range of environmental conditions.…”
Section: Profiling and Trackingmentioning
confidence: 99%
“…A related approach to evaluating molecular level is the characterisation and tracking of marker peptides. An initial analysis of the protein substrate is performed to identify peptides which fulfil selected criteria, such as reproducible extraction and a unique mass within the MS profile of the sample (Grosvenor et al, 2009). Individual marker peptides are then monitored and tracked.…”
Section: Profiling and Trackingmentioning
confidence: 99%